Laboratory Setback Activators and Explosive Suitability for Gun Launch - Ernest BAKER (Wojskowa Akademia Techniczna, 2019)
There is currently no agreed standard methodology for assessing the suitability of explosives for gun launch or for the determination of acceptance criteria for explosive fill defects. Laboratory setback activator testing has been used as an assessment tool for investigating the suitability of explosives for gun launch. Unfortunately, laboratory setback activator testing is not standardized and large variations exist in activator design, function, and results between different laboratories. However, it is the only currently available tool for assessing an explosives safety and suitability to launch-induced setback forces. In laboratory setback activator tests, ignitions are observed at setback loadings that are much higher than produced in actual gun launched projectiles. This may be related to the defects in actual projectiles, which appear to be very different than the laboratory tests.
Keywords: Bezpieczeństwo eksploatacji amunicji